The new rules of sales and service : how to use agile selling, real-time customer engagement, big data, content, and storytelling to grow your business - Scott, David Meerman (Wiley, 2014)
Sales and service are being radically redefined like never before. With buyers now in possession of unlimited information, online content is quickly becoming the dominant driver for commerce. Today anyone working in sales or customer service needs to possess entirely new skills. Unfortunately most organizations are still using traditional selling and service models developed for a different time. In this new book by the author of the #1 bestseller The New Rules of Marketing & PR, David Meerman Scott demystifies the new digital commercial landscape and offers inspiring and valuable guidance f.